En utvärdering av avelsprogrammet mot kronisk hjärtklaffsdegeneration hos Cavalier King Charles spaniels - Lundin, Tobias (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2008)
Chronic valvular disease (CVD) is the most common cardiac disease in dogs, which account for 75% of all the cardiac cases. Cavalier King Charles spaniel (CKCS) is the most affected breed and it´s 13th times more likely that a CKCS, between the age of 7-10 years, will die or be euthanized for cardiac disease, compared with other breeds. The prevalence has been proven to bee independent of coat color and weight but highly dependent on age and gender in CKCS.